Respostas

2014-05-13T10:47:20-03:00
– x² + 3x + 10 = 0 em bhaskara, o 2.a é = 2.(-1) ?

- x² + 3x + 10 = 0
a= -1
b= 3
c= 10
Δ= b² - 4ac
Δ= (3)² -4(-1)(10)
Δ= 9 + 40
Δ= 49
se
Δ>0
então
x = - b - + 
√Δ/2a

x' = -3 -√49/2(-1)
x' - 3 - 7/-2
x' = -10/-2  ATENÇÃO (-):(-) = (+)
x' = + 5

x" = -3 + √49/2(-1)
x" = - 3 + 7/-2
x" = 4/-2  atenção (+) : (-) = (-)
x" = - 2

verificação PARA TIRAR A DUVIDA??
substituir as raízes
x'= + 5 
-X² + 3x + 10 = 0
-(5)² + 3(5) + 10 = 0   atenção  -(5)² ≠ (-5)²
                                                    -(5)² = - 25     e   (-5)² = + 25 
- 25 + 15 + 10 = 0
- 25 + 25 = 0
         0     = 0

x" = - 2
- x² + 3x + 10 = 0
-(-2)² + 3(-2) + 10 = 0
-(4) - 6 + 10 = 0
- 4 - 6 + 10 + 0
-10 + 10 = 0
         0 = 0

REALMENTE SOLUÇÃO = S ={-2; 5}

espero ter esclarecido????